Pengembangan Instrumen Penilaian Berbasis Quizizz Untuk Mengukur Kompetensi Pengetahuan Fisika Siswa - Elisa Elisa; Aslamiyah Rambe; Ainun Mardiyah; Tina Anggaraini Siregar; Roipalah Roipalah; Fatma Zunastri (Mahesa Research Center, 2021)
The purpose of this research is to develop a quiz-based assessment tool that can measure students' competence in physics. This research is a type of research on the development of a 4-D model (four-D model) which consists of four stages, namely: definition, design, development and dissemination. The results of the development research got validation results from linguists with an average of 3.57, a percentage of 89% and a